الصراع حول زعامة الإسلام السياسي في الجزائر بعد حراك فيفري 2019م - ناش, رضوان (University of Eloued جامعة الوادي, 2020)
ملخص: عرفت الأحزاب السياسية الإسلامية الجزائرية تنافسا كبيرا حول كراسي التمثيل السياسي، وكانت تعتقد أنها الكتلة الشعبية الأكبر باعتبار انتماء غالبية الشعب الجزائري إلى التدين، لكن الحراك الشعبي أسقط هذا الاعتقاد الحزبي وأشعل التنافس بين الأحزاب الإسلامية من جديد حول مسألة التمثيل ومدى التأثير في القاعدة الشعبية. Abstract The Algerian Islamic political parties have known a great competition about political representation chairs and she thought that it is the largest popular bloc considering the affiliation of the majority of the Algerian peoples to religiosity but the popular movement dismissed this partisan belief and rekindle the competition between the Islamic parties again on the issue of representation and the extent of influence on the grassroots.
The Struggle Over The Leadership Of Political Islamic In Algeria Often February Movement 2019.
Keywords: Religion ; Algeria ; Party ; Salafia ; الدين ; الجزائر ; حزب ; السلفية